Transcranial magnetic stimultation: scientific and modern technology for treatment of psychiatric and neurological disorders (Bangladesh Journal of Psychiatry, 2017)
Extraordinary advances have been made in the treatment of mental illness. As a result, many mental health disorders can now be treated nearly as successfully as physical disorders. Transcranial Magnetic Stimulation (TMS) is one of the most scientific and modern techniques for treatment of neuropsychiatric disorders. Recently it has been introduced in Ashiyan Medical College Hospital, Dhaka, Bangladesh. The aim of this review article is to introduce this new intervention and provide a clinically useful update about it. For this purpose twenty three articles were selected through searching internet and then reviewed. This article summarized its use in neuro-psychiatric disorders, mechanism of action, adverse effects and outcome issues. It is used in clinical and research practice around the world by psychiatrists. More research is needed to establish the role of TMS in clinical practice in BangladeshBang J Psychiatry June 2015; 29(1): 41-43